Efficiency of Use of Innovations in Education (American Journal of Public Diplomacy and International Studies (2993-2157), 2023)
In this article, the role of innovative technologies in imparting modern knowledge to young people in the higher education system, the use of advanced pedagogical technologies and modern methods in the course of the lesson, and the improvement of the quality and efficiency of education are explained.